The genetic context of blaIMP varies among bacterial families from One Health sources. - Susan Vaughn Grooters; Dixie F Mollenkopf; Thomas E Wittum (PLoS ONE)
The blaIMP resistance gene encodes a metallo-beta-lactamase in bacteria, which confers reduced susceptibility or resistance to all the beta-lactams, including carbapenems which are critical for treating life-threatening infections. The dissemination of blaIMP among various taxonomic families shows the diversity and range of horizontal gene transfer. Using short-read whole genome sequencing and bioinformatic tools, we determined the genetic motifs surrounding blaIMP present in 32 bacterial isolates recovered from environmental sources and agriculture facilities. blaIMP can be located extra-chromosomally on plasmids or within incomplete and complete Tn7 chromosomal structures. We identified a complete Tn7 transposon harboring the blaIMP-27 gene cassette within a class 2 integron located in chromosomal contigs of Shewanella spp. and Providencia spp. Acinetobacter spp. isolates were observed with truncated and incomplete Tn7 transposons, while conserving the class 2 integron and resistance gene cassettes. Additionally, IncQ1 plasmids carried by Proteus spp., Escherichia coli, and other Enterobacteriaceae spp. harbored class 2 integrons with blaIMP-64 and sat2 resistance gene cassettes. In an Acidovorax sp. isolate, blaIMP-27 and sat2 gene cassettes were found associated with an insertion sequence, ISL3 transposase, in an RP4 plasmid. The conserved structure of Tn7 in Shewanella spp. and Providencia spp. is consistent with these species being potential reservoirs from which other bacterial species have acquired partial Tn7 motifs, and the blaIMP-27 gene cassette. These data contribute to a broader understanding of the dissemination and temporality of blaIMP alleles and their mobile genetic elements.